The best American humorous short stories - Jessup, Alexander, 1871- (Floating Press, 2009)
The Best American Humorous Short Stories features tales from Oliver Wendell Holmes, Edgar Allan Poe, Mark Twain and many other well known writers. From the editor: This volume does not aim to contain all "the best American humorous short stories"; there are many other stories equally as good, I suppose, in much the same vein, scattered through the range of American literature. I have tried to keep a certain unity of aim and impression in selecting these stories. In the first place I determined that the pieces of brief fiction which I included must first of all be not merely good stories, but good short stories. I put myself in the position of one who was about to select the best short stories in the whole range of American literature, but who, just before he started to do this, was notified that he must refrain from selecting any of the best American short stories that did not contain the element of humor to a marked degree. But I have kept in mind the wide boundaries of the term humor, and also the fact that the humorous standard should be kept second - although a close second - to the short story standard.